Practical Reiki : A Step-by-Step Guide - Hall, Dr. Mari (London Thorsons, 1997)
Practical Reiki is a fully illustrated, complete guide to Reiki, the universal life-giving energy system.
Includes Bibliography and Illustrations.
"A practical step by step guide to this ancient healing art"--Cover.
Keywords: Reiki (Healing System) -- Alternative Medicine